Metagenome Sequence Analysis of Filamentous Microbial Communities Obtained from Geochemically Distinct Geothermal Channels Reveals Specialization of Three Aquificales Lineages - Takacs-vesbach, Cristina; Inskeep, William P.; Jay, Zackary J.; Herrgard, Markus J.; Rusch, Douglas B.; Tringe, Susannah G.; Kozubal, Mark A.; Hamamura, Natsuko; Macur, Richard E.; Fouke, Bruce W.; Reysenbach, Anna-Louise; McDermott, Timothy R.; et al. (Frontiers in Microbiology, 2013)
The Aquificales are thermophilic microorganisms that inhabit hydrothermal systems worldwide and are considered one of the earliest lineages of the domain Bacteria. We analyzed metagenome sequence obtained from six thermal ‘filamentous streamer’ communities (~40 Mbp per site), which targeted three different groups of Aquificales found in Yellowstone National Park (YNP). Unassembled metagenome sequence and PCR-amplified 16S rRNA gene libraries revealed that acidic, sulfidic sites were dominated by Hydrogenobaculum (Aquificaceae) populations, whereas the circumneutral pH (6.5 - 7.8) sites containing dissolved sulfide were dominated by Sulfurihydrogenibium spp. (Hydrogenothermaceae). Thermocrinis (Aquificaceae) populations were found primarily in the circumneutral sites with undetectable sulfide, and to a lesser extent in one sulfidic system at pH 8. Phylogenetic analysis of assembled sequence containing 16S rRNA genes as well as conserved protein-encoding genes revealed that the composition and function of these communities varied across geochemical conditions. Each Aquificales lineage contained genes for CO2 fixation by the reverse TCA cycle, but only the Sulfurihydrogenibium populations perform citrate cleavage using ATP citrate lyase (Acl). The Aquificaceae populations use an alternative pathway catalyzed by two separate enzymes, citryl CoA synthetase (Ccs) and citryl CoA lyase (Ccl). All three Aquificales lineages contained evidence of aerobic respiration, albeit due to completely different types of heme Cu oxidases (subunit I) involved in oxygen reduction. The distribution of Aquificales populations and differences among functional genes involved in energy generation and electron transport is consistent with the hypothesis that geochemical parameters (e.g., pH, sulfide, H2, O2) have resulted in niche specialization among members of the Aquificales.